BioMOF coupled with plasmonic CuNPs for sustainable CO2 fixation in cyclic carbonates at ambient conditions. (March 2023) - Erzina, Mariia; Guselnikova, Olga; Elashnikov, Roman; Trelin, Andrii; Zabelin, Denis; Postnikov, Pavel; Siegel, Jakub; Zabelina, Anna; Ulbrich, Pavel; Kolska, Zdenka; Cieslar, Miroslav; Svorcik, Vaclav; et al.
Abstract: To improve the actual environmental situation, in closing the loop of carbon dioxide (CO2 ) cycle by reutilization, the CO2 activation is necessary. The energy inputs for that should be economically viable and renewable, while the catalyst(s) should come from naturally abundant elements and building blocks. Important should be also technological simplicity of CO2 activation and environmental friendliness of used chemicals. In this work, we propose a promising solution for CO2 reutilization based on plasmon-assisted photocatalysis using CuNPs and MOF, based on L -glutamic acid and Zn ions (ZnGlu). ZnGlu crystals were hybridized with CuNPs to introduce plasmon-related (photo)absorption bands at visible wavelengths. ZnGlu is responsible for catalytic activity, triggered by the high-energy field of plasmonic dipoles of CuNPs. The proposed catalyst was used for CO2 cycloaddition with different reactivity forming corresponding carbonates and meets the following criteria: catalyst's material-copper, light as a renewable energy source, functionality at normal temperature and pressure. Graphical Abstract: ga1 Highlights: Plasmon-assisted photocatalysis via CuNPs and MOF for CO2 cycloaddition to epoxides. Nature elements alone in hybrid catalyst structure. Solvent-free CO2 cycloaddition at room temperature and atmospheric pressure. Plasmonic coupling between CuNPs as key for the photoefficiency of the catalysts. Cycloaddition on a number of epoxides with growing organic substrate complexity.